Development of Digital Cognitive Learning Media on Magnetism Material to Empower Problem-Solving Skills of Fourth Grade Elementary School Students - Rizki Pratama, I Putu Fradeo Surya; Utama, Candra; Thohir, Muhammad Anas (Proceedings Series of Educational Studies, 2024)
This research aims to develop an interactive digital guide for magnetism experiments to empower problem solving skills among fouth-grade school students. The guide is intended to be valid according to experts, practical for users, and effective in enchancing students problem solvinf abilities. The research follows the five stage of the ADDIE Model, which are analysis, design, development, implementation, and evaluation. Data analysis techniques include both qualitative and quantitative methods. The result of this media development project show that the material validation achieved a score of 98%, media validation reached 98% and user validation received 99%, all categorized as highly valid. In terms of practically during testing phase, a percentage of 98,67% was obtained, indicating a high level of practicality. Therefore, the research and development of this interactive digital guide for magnetism ecperiments, designed to enchance problem solving skills among fourth-grade elementary school students, is highly valid according to experts in the field, practical according to users, and effective according to students. Keywords: Experiment Guide, Magnetism, Problem solving, Media